Islamic Education: The Main Path of Islamization in Southeast Asia - Nurbaiti, Nurbaiti (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
The debate about the arrival of Islam in Southeast Asia is usually related to three main issues, i.e., the time and place of origin of the arrival of Islam, and the person who brought the religion. At least, there are four main theories about the origins of Islam in the Archipelago, which are debated in discussing the arrival, spread, and Islamization of the Archipelago, i.e., “Indian Theory,” “Arabic Theory,” “Persian Theory,” and “Chinese Theory.” This study intends to examine the main pathway of Islamization through Islamic Education in Southeast Asia, then the political development of Islamic Education in Southeast Asia, and the challenges faced by Islamic schools in Southeast Asia. This research uses a qualitative method with the type of literature study. The results showed, first, that trade and ulama were moderating variables at the beginning of Islamization in the Archipelago, while the primary variable was Islamic Education taught by Ulama and traders who came to this region to the local population. Second, the development of Islamic Education is different from one country to another. This is undoubtedly influenced by the geographical location, the culture of society, to politics that influenced the existence of these differences. Third, school development, especially in Indonesia, is understood as a social movement that did not only succeed in educating students but also formed a network of social ideologies that would later influence social transformation, even national development. The implications of this study provide a deeper understanding of the History and dynamics of Islamic Education in Southeast Asia.